PENGARUH ELECTRONIC WORD OF MOUTH (eWOM), PERCEIVED ENJOYMENT, DAN SUBJECTIVE NORM TERHADAP PURCHASE INTENTION JASA SUBSCRIPTION VIDEO ON DEMAND (SVoD) NETFLIX DENGAN VARIABEL PERCEIVED USEFULNESS SEBAGAI VARIABEL MEDIASI (SURVEI PADA GENERASI Z DI DAERAH ISTIMEWA YOGYAKARTA) [THE EFFECT OF ELECTRONIC WORD OF MOUTH (eWOM), PERCEIVED ENJOYMENT, AND SUBJECTIVE NORM ON PURCHASE INTENTION IN SUBSCRIPTION VIDEO ON DEMAND (SVoD) SERVICE NETFLIX WITH PERCEIVED USEFULNESS AS MEDIATING VARIABLE (SURVEY O - Taqiyya Salmanajah Kusumawati; Agung Satmoko (Indonesian Marketing Journal, 2023)
This study aims to explain the effect of electronic word of mouth (eWOM), perceived enjoyment, and subjective norm, on the purchase intention of the Netflix streaming platform for generation Z in the Special Region of Yogyakarta with the mediated variable of perceived usefulness. Technological advances abreast with the literacy of the next generation towards technology. The research method used in this research is quantitative research with survey method. The research sampling technique used non-probability in the form of purposive sampling with the criteria is generation Z in the age range of 17 - 26 years has never subscribed to Netflix. The analytical tool used in this research is Smart PLS 3.2.9. The research data was collected through a questionnaire and 131 respondents were obtained. The results of this study indicate that: (1) electronic word of mouth (eWOM), subjective norm, and perceived usefulness have a positive effect on purchase intention, while perceived enjoyment has no effect on purchase intention; (2) perceived enjoyment and subjective norm have a positive effect on perceived usefulness, while electronic word of mouth (eWOM) has no effect on perceived usefulness; (3) there is a positive effect on the indirect effect of perceived enjoyment and subjective norm on purchase intention through perceived usefulness, while electronic word of mouth (eWOM) has no effect on purchase intention through perceived usefulness.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk menjelaskan mengenai pengaruh electronic word of mouth (eWOM), perceived enjoyment, dan subjective norm, terhadap purchase intention platform streaming Netflix pada generasi Z di Daerah Istimewa Yogyakarta dengan dimediasi variabel perceived usefulness. Kemajuan teknologi beriringan dengan meleknya generasi penerus terhadap teknologi. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dengan metode survey. Teknik pengambilan sampel penelitian menggunakan non-probability berupa purposive sampling dengan kriteria merupakan generasi Z di rentang umur 17 – 26 tahun, dan belum pernah berlangganan Netflix. Alat analisis yang digunakan penelitian ini merupakan Smart PLS 3.2.9. Data penelitian dikumpulkan melalui kuesioner dan diperoleh 131 responden. Hasil penelitian ini menunjukkan bahwa: (1) electronic word of mouth (eWOM), subjective norm, dan perceived usefulness berpengaruh positif terhadap purchase intention, sedangkan perceived enjoyment tidak berpengaruh terhadap purchase intention; (2) perceived enjoyment dan subjective norm berpengaruh positif terhadap perceived usefulness, sedangkan electronic word of mouth (eWOM) tidak berpengaruh terhadap perceived usefulness; (3) terdapat pengaruh positif atas pengaruh tidak langsung perceived enjoyment dan subjective norm terhadap purchase intention melalui perceived usefulness, sedangkan electronic word of mouth (eWOM) tidak berpengaruh terhadap purchase intention melalui perceived usefulness.